Best practice in symptom assessment: a review. (13th April 2004) - McColl, E
Abstract : Assessment of symptoms is important both in the diagnosis of gastro-oesophageal reflux disease (GORD), and in monitoring response to therapeutic interventions. Key quality aims in assessing symptoms are to gather data that are valid, reliable, unbiased, discriminating, and responsive to change. Important considerations include who should assess symptoms, method of data collection, timing of assessment, and methods of assessing multiple symptoms.